Structural And Optical Properties Of AlxInyGa1-x-yN Thin Films - Abed, Muslim A. (2012)
The studies focus on the investigations of the structural and optical properties of three sets of nitride thin films. The first set is InxGa1-xN (0.2 ≤ x ≤ 0.8) ternary nitride, the other two sets are AlxInyGa1-x-yN quaternary nitrides, the first one with constant Al, x = 0.06, and In in the range of 0 ≤ y ≤ 0.10, while the second set is with constant In, y = 0.10, and variable Al composition ranging from 0 ≤ x ≤ 0.20. As well as the study of the zone-center optical phonon modes, especially the A1(LO), E1(TO), E2(Low) and E2(High) modes for ternary and quaternary nitride materials theoretically using pseudo unit cell (PUC) model and experimentally using Raman and FTIR spectroscopy. The ternary and quaternary films were grown on c-plane (0001) sapphire substrates with AlN as buffer layers using plasma assisted molecular beam epitaxy (PA-MBE) technique. The structural and optical properties of the ternary and quaternary nitride semiconductors have been investigated by several non-contact and non-destructive equipments, which include structural characterizations such as scanning electron microscopy (SEM), energy dispersive X-ray (EDX), atomic force microscopy (AFM) and high resolution X-ray diffraction (HR-XRD), while the optical characterizations include, spectral reflectance technique, ultraviolet-visible (UV-VIS) spectroscopy, photoluminescence (PL) spectroscopy, Raman spectroscopy and polarized infrared (IR) reflectance spectroscopy.